Faktor Risiko Anemia pada Wanita Pemetik Teh - Eryasih Setyorini; Faisal Anwar; Hadi Riyadi; Ali Khomsan (Media Kesehatan Masyarakat Indonesia, 2019)
Anemia is known as a public health problem for many years, based on the results of Riskesdas 2018 it isknown that the prevalence of anemia is 48.9%. This research aims to analyze the risk factors that influence anemiain female tea pickers in Pangalengan, Bandung, West Java. The research method was cross-sectional with 148subjects of the so-called Wanita Usia Subur (WUS). They are women of childbearing age, between 18-45 yearsold who were married and not pregnant. They were selected purposively in the plantation areas Purbasari, TalunSantosa and Sedep. This research was part of a research funded by Neys-van Hoogstraten Foundation (NHF).The data obtained are the characteristics of the subjects (age, family size, length and level of education), monthlyfamily expenses for food and non-food, status of nutrition and body composition, and anemia status. The resultsshowed that most of the female tea pickers are 40-44 years old, having family size up to 4 people and 72.3% ofthem are low level educated (89.9% has maximum the elementary school education). The average expenses fornon-food are greater than those for food. Based on various body composition indicators, the female tea pickerswere in general overweight (56.8%), normal upper arm circumference (98.6%). The average total of body fat isgreater than 32,1%, normal visceral fat (≤9%), waist circumference at risk ≥80 cm, and RPP ≥0.8 cm at 81.1%.The prevalence of anemia in tea picking women was 42.6%. Overweight is the most risk factor for anemia becausefat accumulation can reduce iron absorption so that the amount of hemoglobin goes down and erythrocytesdecreases. The age as a protective factor. Anemia can be prevented through nutrition education, healthy lifestyles,and controlling the causes and predisposing factors.